The motivational needs and value orientations of Filipino academic and research librarians - Pagaduan, Ma. Chloe Rochelle C. (2003)
The study seeks to determine the operating need level of academic and research librarians, in the context of Maslow's Hierarchy of Needs Theory. It also aims to determine the value dimension of the respondents in the context of the studies done by Hofstede and Mendonca & Kanugo. These value dimensions include Power Distance, Uncertainty Avoidance, Masculinity, Individualism, Paternalism and Associative Thinking.